006 PP: COLLABORATION IN MUSEUMS AND HEALTH RESEARCH. (3rd March 2017) - Morse, N; Lockyer, B; Camic, PM; Thomson, LJ; Chatterjee, HJ
Abstract : This study reflects on the range of collaborations in two distinct but thematically linked UCL research projects which consider the role of culture in health promotion: Museums on Prescription (2014–2017), in partnership with Canterbury Christ Church University, explores the value of heritage encounters in social prescribing for lonely older adults at risk of social isolation; and Not So Grim Up North (2016–2018), in conjunction with Whitworth Art Gallery, University of Manchester and Tyne & Wear Archives & Museums, investigates the health and wellbeing impacts of museum activities for stroke survivors; older adults with dementia; and mental health and addiction recovery service-users. Both projects employ a mixed-methods approach using quantitative and qualitative data. The research projects have been developed and delivered through collaborations between interdisciplinary university researchers, museum practitioners, health and social care professionals and end-users. Collaboration has taken different forms including co-developing evaluation methods, co-disseminating outputs, and through advisory boards. This study reflects on the opportunities and challenges of collaboration, noting the language and practice dissonance across different fields and the importance of finding common ground. It also highlights the considerable amount of time that is required to build genuine collaborative relationships, which is not often acknowledged in research outputs.